Receptor binding protein of prophage reversibly recognizes the low-molecular weight subunit of the surface-layer protein SlpA in Clostridioides difficile - Phetruen, Tanaporn; Chanarat, Sittinan; Janvilisri, Tavan; Phanchana, Matthew; Charoensutthivarakul, Sitthivut; Phothichaisri, Wichuda; Chankhamhaengdecha, Surang (Frontiers in Microbiology, 2022)
Receptor-binding proteins (RBPs) are located at the viral tail and mediate the initial recognition of phage to a specific bacterial host. Phage RBPs have co-evolved with numerous types of host receptors resulting in the formation of a diverse assortment of cognate pairs of RBP-receptors that function during the phage attachment step. Although several Clostridioides difficile bacteriophages have been discovered, their RBPs are poorly described. Using homology analysis, putative prophage-tail structure (pts) genes were identified from the prophage genome of the C. difficile HN10 strain. Competition and enzyme-linked immunosorbent assays, using recombinant PtsHN10M, demonstrated the interaction of this Pts to C. difficile cells, suggesting a role as a phage RBP. Gel filtration and cross-linking assay revealed the native form of this protein as a homotrimer. Moreover, truncated variants indicated that the C-terminal domain of PtsHN10M was important for binding to C. difficile cells. Interaction of PtsHN10M was also observed to the low-molecular weight subunit of surface-layer protein A, located at the outermost surface of C. difficile cells. Altogether, our study highlights the function of PtsHN10M as an RBP and potentially paves the way toward phage engineering and phage therapy against C. difficile infection.